Richness and Diversity of Phlebotomine Sand Flies (Diptera: Psychodidae) in North Khorasan Province, Northeast of Iran - Kourosh Arzamani; Hassan Vatandoost; Yavar Rassi; Amir Ahmad Akhavan; Mohammad Reza Abai; Mohammad Alavinia; Kamran Akbarzadeh; Mehdi Mohebali; Sayena Rafizadeh (Tehran University of Medical Sciences, 2018)
Background: We aimed to determine the species composition, richness and diversity indices of the Phlebotomine sand flies at different topographic condition in visceral (VL) and cutaneous leishmaniasis (CL) foci in the northeast of Iran. Methods: This cross-sectional study was conducted during 2016 in North Khorasan Province. The sampling was focused on rural regions, where human cases of VL and/or CL were diagnosed and reported during last 5 years. Sand flies were collected three times each twenty days during peak periods of seasonal activity. Seven collection methods were used. Some Alpha and Beta diversity indices were calculated. Results: Overall, 7253 sand flies were collected and identified. They were from 19 species of Phlebotominae sandflies. Phlebotomus sergenti and Ph. papatasi were the most prevalent (84.9%) species in the study area. Species richness (S) was very different in three areas and were18, 8, and 4 respectively but Evenness (E) were 0.357, 0.345, and 0.380, so evenness was almost equal in the study areas. Shannon Index (H ) and Margalef Richness Index were calculated 1.033, 0.718, 0.527 and 2.117, 0.8998, 0.4006 respectively. Conclusion: The sand fly fauna in North Khorasan Province was very rich and often included some of the most important proven or suspected vectors of leishmaniasis. Species diversity indices (Shannon index, and Simpson's index) were not high due to decreasing in evenness. The Margalef richness index could accurately reflect the biodiversity of sand flies between three subtidal locations.